2013
DOI: 10.4172/2157-7048.1000160
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Demethylation of Lignin from Woody Biomass using Biophysical Methods

Abstract: Demethylation of softwood kraft lignin from woody biomass to improve the hydroxyl number in modified demethylated lignin and to produce lignin-based polyols was investigated using several biophysical techniques. Lignin is a tremendously underdeveloped natural polymer co-generated through papermaking and biomass fractionation. Molecular weights of lignins were analyzed by high-performance size-exclusion chromatography (HPSEC). Molecular weights of softwood kraft lignin (SKL) and demethylated lignin (DL) were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It has been reported that the methoxyl groups at the ortho positions to the aromatic hydroxyl in the nine-carbon unit of lignin will hinder the reactivity of its free phenolic hydroxyl groups. If the –OCH 3 groups could be removed and demethylated, the demethylated lignin products would have far more free phenolic groups and its reactivity could be significantly enhanced [ 13 ]. Previous works reported that methoxyl groups in lignin were removed through a nucleophilic substitution reaction when the aryl methyl ethers were attacked by nucleophiles such as S and HS − , resulting in demethylated lignin with lower content of methoxyl groups and higher content of phenolic hydroxyl groups [ 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the methoxyl groups at the ortho positions to the aromatic hydroxyl in the nine-carbon unit of lignin will hinder the reactivity of its free phenolic hydroxyl groups. If the –OCH 3 groups could be removed and demethylated, the demethylated lignin products would have far more free phenolic groups and its reactivity could be significantly enhanced [ 13 ]. Previous works reported that methoxyl groups in lignin were removed through a nucleophilic substitution reaction when the aryl methyl ethers were attacked by nucleophiles such as S and HS − , resulting in demethylated lignin with lower content of methoxyl groups and higher content of phenolic hydroxyl groups [ 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the –OCH 3 groups could be removed and demethylated, the demethylated lignin products would have far more free phenolic groups and its reactivity could be significantly enhanced [ 13 ]. Previous works reported that methoxyl groups in lignin were removed through a nucleophilic substitution reaction when the aryl methyl ethers were attacked by nucleophiles such as S and HS − , resulting in demethylated lignin with lower content of methoxyl groups and higher content of phenolic hydroxyl groups [ 13 , 19 ]. However, the rigid reaction condition obstructed their industrial applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the chemical reactivity of demethylated lignins was enhanced through diminishing methoxyl group content while increasing hydroxyl group content. With the lignins demethylated under optimum reaction conditions, the bonding strength of lignin-based phenolic resins increased while the formaldehyde emissions decreased [64][65][66].…”
Section: Mechanical Properties Of Particleboardsmentioning
confidence: 99%
“…The best results in terms of an increase in OH content and use for PF resins was the sample demethylated with Na 2 SO 3 . Other authors used Na 2 SO 3 for demethylation performed under high-pressure reactors [39] or under reflux [15,40]. Podschun et al chose a different approach in which organosolv lignin was demethylated under microwave radiation [41].…”
mentioning
confidence: 99%